PENGEMBANGAN PRODUK JAMUR KUPING (Auricularia auricula): ACAR DAN KERIPIK - Inneke, Hantoro; Ita, Sulistyawati; Kartika Puspa, Dwiana; Sih Mirmaning, Damar Endah (Seri Kajian Ilmiah, 2014)
Wood ear mushroom (Auricularia auricula) with its high fiber, springy texture and unique flavor is potential to be developed for high economical value processed food. This research aims to develop wood ear mushroom processed food, which are pickled mushroom and chips. The product development includes optimization of formulation and processing. The pickle was made in two brine concentrations (7,5% and 10%) and packed in Poly Ethylene (PE) plastic cups. During three weeks refrigeration, visual observation, the acidity level, color (using Chromameter CR 400 Konica Minolta) and total counts were measured weekly. For mushroom chips, there were five formulations of coating mixed flour (A: 100% wheat flour; B: 75% wheat flour : 25% rice flour; C: 75% wheat flour : 25% sagoo flour ; D: 50% wheat flour: 25% rice flour: 25% sagoo flour and E: 50% wheat flour : 50% sagoo flour). The chips were measured for the break strength (using Texture Profile Analysis by Loyyd Texture Analyzer), sensory evaluation (using hedonic ranking test) and proximate analysis. The result revealed that the recommended pickled mushroom was P10, which pretreated by soaking in 0.1% citric acid + 0.1% sodium metabisulfite and soaked in 10% brine solution since it has the longest shelf-life (two weeks in the refrigerator). Wood ear mushroom chips D which was coated with wheat flour: rice flour: sagoo flour 50%: 25%: 25% was the most preferred by the panelists